A Mesophilic Aeromonas salmonicida Strain Isolated from an Unsuspected Host, the Migratory Bird Pied Avocet - Antony T. Vincent (Microorganisms, 2019)
Aeromonas salmonicida is a Gram-negative bacterium, known as a fish pathogen since its discovery. Although the species was initially considered psychrophilic, a mesophilic subspecies (pectinolytica) and many other mesophilic strains still not attributed to subspecies have been described in the last two decades. These mesophilic strains were sampled from various sources, including humans, and some of them are known to be pathogenic. In this study, we describe a strain, JF2480, which was isolated from the spleen, and also found the kidney and liver of a dead pied avocet (Recurvirostra avosetta), a type of migratory bird inhabiting aquatic environments. A core genome phylogenomic analysis suggests that JF2480 is taxonomically distant from other known A. salmonicida subspecies. The genome sequence confirms that the strain possesses key virulence genes that are present in the typical A. salmonicida psychrophilic subspecies, with the exception of the genes encoding the type three secretion system (T3SS). Bacterial virulence assays conducted on the surrogate host Dictyostelium discoideum amoeba confirmed that the strain is virulent despite the lack of T3SS. Bacterial growth curves showed that strain JF2480 grow well at 40 °C, the body temperature of the pied avocet, and even faster at 41 °C, compared to other mesophilic strains. Discovery of this strain further demonstrates the extent of the phylogenomic tree of this species. This study also suggests that A. salmonicida can infect a wider array of hosts than previously suspected and that we need to rethink the way we perceive A. salmonicida’s natural environment.